Dragon goes house-hunting. Volume 6 - Tanuki, Kawo; Campbell, T (Seven Seas Entertainment, LLC, 2021)
After touring a whole bunch of spectacularly defective houses, it's obvious that Letty's new realtor is pretty bad at his job. And a vampire. So is it really a big surprise that he's turned out to be a villain too? Letty might be harmless, but his reputation as the "Flame Dragon King" just keeps getting him in more and more hot water! -- from publisher.